Pigmented purpuric dermatosis or mycosis fungoides: A diagnostic dilemma - Najeeba Riyaz; Sarita Sasidharanpillai; Ettappurath N Abdul Latheef; Hena Davul; Febin Ashraf (Wolters Kluwer Medknow Publications, 2016)
Pigmented purpuric dermatoses (PPD), a group of vascular disorders with variable clinical picture is reported in all races and age groups with a male predilection. There are reports of mycosis fungoides manifesting as pigmented purpura as well as progression of PPD to cutaneous T-cell lymphoma. The diagnostic dilemma is compounded by PPD manifesting histological similarity to mycosis fungoides. Currently, it is believed that PPD with monoclonal T-cell population is more likely to progress to malignancy. We report a 31-year-old male patient who presented with the lichenoid clinical variant of PPD lesions that mimicked mycosis fungoides on histopathology. Gene rearrangement studies identified a polyclonal T-cell population. The patient responded to photochemotherapy, which is beneficial in both PPD and mycosis fungoides. Our case signifies the limitations of current diagnostic modalities in accurately distinguishing PPD from cutaneous lymphoma. Data on disease progression in similar cases may enable us to formulate better diagnostic definitions.